2004
DOI: 10.1242/jeb.00925
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induces both pyruvate kinase and Na+/H+exchanger activity through protein kinase C mediated signal transduction, in isolated digestive gland cells ofMytilus galloprovincialis(L.)

Abstract: SUMMARYThe present study investigates the transduction pathway mediated by cadmium in isolated digestive gland cells of mussel Mytilus galloprovincialis. The effects of cadmium treatment on a key glycolytic enzyme, pyruvate kinase (PK), and on Na+/H+ exchanger activity were examined. Cadmium (50 μmol l–1) caused a significant elevation of intracellular pH (pHi) and a rise (176%) of Na influx relative to control values. The amiloride analogue, EIPA (20 nmol l–1), a Na+/H+ exchanger blocker,together with cadmium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
4
21
0
3
Order By: Relevance
“…Previously published studies have shown the activation of NHE by heavy metals in HT 29 cells (Hershfinkel et al, 2001) as well as in haemocytes, digestive gland, gills and mantle/gonad cells of mussels (Dailianis and Kaloyianni, 2004;Kaloyianni et al, 2005;Kaloyianni et al, 2006). In addition, it has been reported that activation of NHE enhances ROS production, after exposure to micromolar concentrations of Cd Koutsogiannaki et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previously published studies have shown the activation of NHE by heavy metals in HT 29 cells (Hershfinkel et al, 2001) as well as in haemocytes, digestive gland, gills and mantle/gonad cells of mussels (Dailianis and Kaloyianni, 2004;Kaloyianni et al, 2005;Kaloyianni et al, 2006). In addition, it has been reported that activation of NHE enhances ROS production, after exposure to micromolar concentrations of Cd Koutsogiannaki et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The Cd concentration used was within the range of Cd levels found in Thermaikos Gulf (HCMR, 1997). Moreover, similar concentrations of Cd have been used in other studies, investigating the effects of the metal on cell signalling and its ability to induce cellular toxic effects (Coogan et al, 1992;Misra et al, 1998;Olabarrieta et al, 2001;Pruski and Dixon, 2002;Dailianis and Kaloyianni, 2004;Dailianis et al, 2005;Dailianis, 2009). Specifically, haemocytes were pre-incubated for 20min with either 0.01mmoll -1 forskolin, an adenylyl cyclase (AC) activator, 2moll…”
Section: Experimental and Exposure Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Tales niveles de Cd presentes en mejillones y en su entorno crean expectativas sobre las estrategias bioquímicas de defensa en organismos contaminados, en especial en su adaptación a sobrevivir a la anoxia. Distintos estudios han considerado que el Cd puede provocar daños a nivel molecular en los organismos marinos en bajas concentraciones, conllevando a alteraciones en el trasporte a través de las membranas biológicas (Dailianis & Kaloyianni, 2004), actividad enzimática (Canesi et al, 1998;Nusetti et al, 2010), producción energética (Sokolova, 2004) y daños oxidativos (Prakash & Jagannatha-Roa, 1995;Rajkumar & Milton, 2011).…”
Section: Introductionunclassified